Stability and consistency of metamemory judgments within a session - Yeung, Michael K. (Frontiers in Psychology, 2022)
There has been much interest in assessing individual and group differences in metamemory skills. These endeavors require or would benefit from enhanced knowledge about the stability and consistency of metamemory judgments over successive trials. However, few studies have examined these aspects. Thus, the present study investigated and compared the within-session stability and consistency of three major types of metamemory judgment: judgment of learning (JOL), feeling-of-knowing judgment (FOK), and retrospective confidence judgment (RCJ), using a single-task paradigm. Thirty-eight healthy young adults (17 males, 21 females) completed three trials of a face–scene associative learning task designed to assess metamemory. In each trial, participants rated their JOLs while studying a new set of face–scene pairs, and then rated their FOKs and RCJs while their memory was being tested. The stability and consistency of the mean confidence ratings and the relationships between confidence rating and memory performance, indexed by two gamma estimates, were analyzed and compared across types of metamemory judgments. Over trials, there was a significant decrease in the mean rating for JOL but not for FOK or RCJ. Also, the gamma scores of JOL, but not that of FOK or RCJ, significantly improved with practice. Furthermore, for each type of metamemory judgment, the mean confidence rating showed excellent consistency across trials. Depending on the judgment type and gamma estimation method, the consistency of gamma scores ranged from poor to excellent. Thus, the present study clarified the temporal dynamics of various types of metamemory judgments and the consistency of metamemory measures.